Preparation of Ge-Sb-Te Thin Films by Tellurization of Ge-Sb Thin Film for Phase-Change Random-Access Memory Application. (1st January 2019) - Han, Byeol; Kim, Yewon; Kim, Yu-Jin; Cho, Mann-Ho; Rha, Sa-Kyun; Lee, Won-Jun
Abstract : We report the preparation of crystalline Ge-Sb-Te (GST) compounds by pulsed tellurization annealing of amorphous sputtered Ge-Sb films in a di(tert-butyl)tellurium [( t Bu)2 Te] atmosphere. The cycle of feeding ( t Bu)2 Te into the annealing chamber for 1 s and then pumping down for 60 s was repeated, which was to avoid tellurium deposition. We investigated the effect of annealing temperature and annealing cycle number on the composition and crystal structure of GST thin films. The thin film was not wholly tellurized at 160 or 190°C, while the entire film was uniformly tellurized and crystallized at 220°C to form a GST film having a composition ratio close to that of Ge1 Sb2 Te4 . The phase change temperature gradually decreased as tellurization proceeded. In the case of 30 cycles at 220°C, in which the entire Ge-Sb film was tellurized, the resistance reduction was observed at 150°C. The diffusion of germanium from GST into the substrate was also discussed.